The politics of climate risk assessment - Johanna Hedlund (npj Climate Action, 2023)
Abstract Almost 25 years ago, sociologist Anthony Giddens wrote that ‘risk and responsibility are in fact closely linked’1. Extending this to climate risk, this perspective paper argues that climate risk assessment is not just a scientific endeavour but also deeply political. As climate risks become more complex and demand more science- and policy-driven integration across sectors and regions, assessments may involve significant political constraints that impede effective and just climate adaptation. Using a framework of integration challenges, this paper uncovers political constraints that may arise in developing integrated climate risk assessment. It argues that the framing and structuring of climate risk assessment may yield political constraints such as biases towards certain groups, sectoral incoherence, decisions not aiding the most exposed, distributional conflicts, and ambiguous responsibility in managing complex climate risks. Left unaddressed, such political constraints may hamper climate adaptation rather than enable progress.